117k views
3 votes
If the function f(x)=(2x-3)^3 is transformed to g(x)=(-2x-3)^3 , Wichita type of transformation occurred?

1 Answer

5 votes

Answer: Reflection across the x-axis.

Explanation:

The correct exercise is: The correct exercise is: "If the parent function
f(x) = (2x - 3)^3 is transformed to
g(x) = (-2x + 3)^3 , which type of transformation occurs?

"

There are several transformations for a function f(x). Two of those transformations are shown below:

1. If
-f(x), then the function is reflected across the x-axis.

2. If
f(-x), then the function is reflected across the y-axis.

In this case, the exercise provides you the following function f(x):


f(x) = (2x - 3)^3

And you know that the function g(x) is obtained by transforming the function f(x). The function g(x) is:


g(x) = (-2x + 3)^3

Which can written as:


g(x) = -(2x - 3)^3

Therefore, you can identify (based on the transformations shown at the beginning of the explanation), that:


g(x)= -f(x)

Therefore, the function
g(x) = (-2x + 3)^3 is obtained by reflecting the function
f(x) = (2x - 3)^3 across the x-axis.

User Domgblackwell
by
4.6k points